2012
DOI: 10.1088/1751-8113/45/7/075401
|View full text |Cite
|
Sign up to set email alerts
|

UV/IR mixing as a twisted Poincaré anomaly

Abstract: We analyze symmetries of the 1-loop effective action of φ 4 noncommutative field theory. It is shown, that despite the twisted Poincaré invariance of the classical noncommutative action, its 1-loop quantum counterpart lacks this invariance. Though Noether analysis of the model is somewhat obscure, it is still possible to interpret this symmetry breaking as a quantum anomaly due to inappropriate choice of the quantization method. * apinzul@unb.br 1 IntroductionBased on a quite general argument [1], it is believ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The resulting theory is translationinvariant, but does not possess the properties exposed above for the Grosse-Wulkenhaar model (see also [26,27,28,29]). Some new features can also be found in other noncommutative scalar theories [30,31]. A noncommutative gauge theory involving a harmonic term has been constructed in [32,33], which is therefore strongly related to the Grosse-Wulkenhaar model.…”
Section: Introductionmentioning
confidence: 94%
“…The resulting theory is translationinvariant, but does not possess the properties exposed above for the Grosse-Wulkenhaar model (see also [26,27,28,29]). Some new features can also be found in other noncommutative scalar theories [30,31]. A noncommutative gauge theory involving a harmonic term has been constructed in [32,33], which is therefore strongly related to the Grosse-Wulkenhaar model.…”
Section: Introductionmentioning
confidence: 94%
“…In the case of 3+1-dimensional quantum field theories, it was recently shown that the Lorentz symmetry is restored upon twisting [6]. Despite this insight several outstanding and controversial issues still plague the twisted implementation of the Lorentz symmetry [7]. The first difficulty one encounters is to carry out the standard Noether analysis and to identify conserved charges for the twisted Lorentz symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…This has rather drastic consequences such as the absence of UV/IR mixing. Indeed, in [7] it is argued that UV/IR mixing may be related to a quantum anomaly of the Lorentz group, which is very closely related to the choice of functional integral measure. At this point there seems to be no consensus between these different points of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of (5) the quantum fields written on GM plane, unlike ordinary quantum fields, follow an unusual statistics called twisted statistics. Noncommutative field theories without twisted commutation relations do not preserve the classical twisted Poincaré invariance at quantum level and suffer from UV/IR mixing [8]. The twisted statistics is a novel feature of fields on GM plane.…”
Section: Introductionmentioning
confidence: 99%